Optimizing E-Marketing Using Social Media in Increasing Sales Turnover of Rifles - Teguh Wibowo; Okta Vianur (Cita konsultindo, 2024)
Airguns are popular tools in sports, hunting, or households due to their compact size and low price compared to other items, such as heavy vehicles like cars, etc. Facebook and Instagram are two popular social media platforms in Indonesia. The problem is, consumer interest in purchasing products that have used rifle products is decreasing. This problem is caused by a less than optimal rifle sales strategy. The results of the study also reveal that Facebook is the most powerful media in terms of business practices. The researcher is a businessman who needs a strategy to increase his sales. This research was designed to optimize the use of social networks Facebook and Instagram to increase rifle sales. This research is qualitative research using interview and observation research methods. The analysis method used uses SWOT analysis with five research samples taken based on the closest location criteria. Search Results Build broader relationships within the gun enthusiast and seller community via social media. Create a definite advertising schedule and create content that is safe, engaging and interactive. Calculate a clear budget to set the right price and obtain optimal profits for the market through social networks. Set specific times for editing content and uploading content. Obstacles faced include inadequate availability of equipment and information to produce less than optimal content ideas..